You are poetry? (XXI Century. Spanish Literature and Culture, 2014)
Nobody knows exactly what poetry is. That is why the unsuccessful search of poetry’s being and nature generates resistance in time, despite its flagrant anti-pragmatism. I am aware of this unequaled failure. I have fatigued other’s approximations that could clarify something about. Due to this quest, I offer a little varied sample, for taking account of the wealth and extension of poetic phenomenon. However, it is just possible both affirming something and opposing it, without incurring into a contradiction. I approach the lyrical numen to the religious, even to the mystical. I try to integrate it into theories of knowledge, without delving into them. Finally, I write some notes about how the way I understand all these considerations can be used in a poem’s writing.
Keywords: poetry; Mysticism; Theory of knowledge; poetic; Fermín Herrero